Intercultural Communication : A Contextual Approach - Neuliep, James William, 1957- (Los Angeles : SAGE Publications, 2021)
This resource looks at every aspect of intercultural communication from extensive number of insightful angles, including of contexts such as cultural or ethnic, geographic and situational, covering both verbal and non-verbal interaction, alongside a range of theories and perceptions.
Keywords: Communicatie; Communication